PENGARUH BAHAN PENGISI SILIKA DAN SERBUK TANDAN KOSONG SAWIT (STKS) TERMODIFIKASI TERHADAP KEKUATAN BENTUR DAN DAYA SERAP AIR KOMPOSIT HIBRID POLIESTER TIDAK JENUH - Halimatuddahliana, Johan Evander Sirait, Fermadi Sirait (Jurnal Teknik Kimia USU, 2016)
This research aims to determine the effect of palm oil empty fruit bunches (POEFB) powder and silica into the matrix of unsaturated polyester resin (UPR) and the influence of chemical modification OPEFB with using acetic acid 50% (v / v). In this study, (UPR) was mixed with silica and OPEFB to weight ratio (UPR: Silica: OPEFB) 80: 20: 0, 80: 15: 5, 80: 10: 10, 80: 5: 15, 80: 0: 20 by hand lay-up method. Analysis was done by impact test, and analysis of scanning electron microscopy (SEM). Results showed that impact strength at a ratio of 80: 5: 15 was higher than those without modification viz. 3622.5 J / m2. In this case the chemical modification has lowered OPEFB polarity so that the interfacial tencion between the filler with a matrix became low resulting in good interfacial interaction and adhesion between matrix and fille. Impact strength values ​​were supported by the results of SEM. From water adsorption test, composite with chemical modification showed low values as compared without modification indicating that modification has lowered the polarity of OPEFB.